External Shocks, Exchange Rate Changes, and Intermediate Goods: Explanation of Stagflation in Iranian Economy - Shahbod Seighalani; Seyed Ahmadreza Jalali-Naini; Nasser Khiabani (برنامه‌ریزی و بودجه, 2022)
Explanation of economic cycles, especially stagflation in an oil-dependent economy with high dependency on imported intermediate goods, requires a prototypical representation of the supply side and the propagation mechanism of the external shocks. In commodity-exporting countries, exchange rate changes are often caused by exogenous changes in the terms of trade. Apart from this, external shocks such as international sanctions, restricting foreign trade and increasing transaction costs, not only affect external relative prices but also disrupt the supply chain, thus can be a very strong source of economic cycles or stagflation episodes. External shocks modify investment decisions regarding domestic and foreign assets, significantly affect household consumption and hence the demand side of the economy. Where the final product is highly dependent on imported intermediate goods, negative foreign shocks (i.e. sanctions) can disrupt the supply chain, via the imported intermediate goods channel, and affect output supply price. Therefore, the transmission mechanism of the external shocks in an economy with the above features requires appropriate modeling of both the demand and supply sides. As to explain the observed episodes of stagflation in the Iran’s economy, we expand the supply side of a typical new Keynesian DSGE model by presenting and separating imported and domestic intermediate goods in the production function as components of the supply chain, introducing an extra channel for the impact of external shocks on output, inflation, and consumption.